Alumni’s perceptions about commitment towards their university: drivers and consequences - Pedro, Ilda (2021)
This paper intends to capture alumni's assessments and perceptions about decisive dimensions of their commitment towards their alma mater. Their academic experience and current situation are highlighted. Moreover, their perception about the role of Higher Education Institution (HEI) in this commitment-relationship is likewise valuable to get their involvement. The study took place at a Portuguese university. Three focus groups, with 21 participants, were conducted to get consistent information permitting further developments. Data were analysed through NVivo software.The study gives insights revealing dimensions such as the relationships with teachers, extracurricular activities and initiation as decisive in their academic experience. Recommending and sharing their experience, underline evidence of what they are willing to give back. Moreover, their consciousness of bearing a mission to contribute to HEI's development was expressed through strong positive feelings, such as the sense of belonging, and pride at being part of the university, defined in their statements. But they all demand an effective ability of the university to communicate with them. Overall conclusions offer a scenario of alumni's commitment, giving HEI's management valuable clues to improvement, but its responsibility in this commitment-relationship was also stressed. Moreover, results also provide contributions to literature enabling other HEIs to replicate the study or simply use the results for their own development. Since the study occurred in a relatively weak alumni culture context, revealing the importance in promoting debate as a means to engage alumni in HEI's efforts for success, it presents insights for further developments in similar higher education environments.